1983
DOI: 10.1007/bf01496728
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subsets in the peripheral blood of patients with multiple myeloma and benign monoclonal gammopathy

Abstract: A panel of monoclonal antibodies that identify various antigens present on T and B cells was used to characterize circulating blood lymphocyte subsets in multiple myeloma [(MM)--13 patients] and benign monoclonal gammopathy [(BMG)--5 patients]. In MM and BMG an increase in B cell proportions (BA 1 positive cells) was observed, whereas T cells (Lyt 3 positive cells) were reduced compared to normal controls. However, with respect to the T cell subset distribution, a marked diversity between MM and BMG was noted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
2

Year Published

1984
1984
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
3
5
2
Order By: Relevance
“…Therefore, the OKT4/OKT8 ratio was significantly elevated (Table 3). These results differ from those published so far [9,13,25]. Mellstedt et al [13] reported decreased percentages of OKT4 ÷ lymphocytes both in MM and in BMG with unaltered OKT4/OKT8 ratios.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…Therefore, the OKT4/OKT8 ratio was significantly elevated (Table 3). These results differ from those published so far [9,13,25]. Mellstedt et al [13] reported decreased percentages of OKT4 ÷ lymphocytes both in MM and in BMG with unaltered OKT4/OKT8 ratios.…”
Section: Discussioncontrasting
confidence: 80%
“…DR + lymphocytes of untreated and treated MM were within the normal range, whereas sIg ÷ cells revealed a significant decrease in both groups (P < 0.05), as previously described by Dillman et al [6]. In contrast, there are other reports of normal or elevated B cell counts in MM [9,13,25].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations